Synthesis and characterization of main chain thermotropic liquid crystalline polyesters based on methyl 4-[4 `-(omega-hydroxyalkoxy)blphenyl-4-yl]-4-oxobutyrate: Effects of keto group and connectivity on mesophasic characteristics of biphenyl based AB-typ - Ranganathan, T.; Ramesh, C. (Reactive & Functional Polymers, 2006)
A series of biphenyl based main chain thermotropic liquid crystalline polyesters, poly(hydroxyalkoxybiphenyl oxobutyrate) [PRBOB-2,n (n = 2-8)], containing various methylene spacers was synthesized by using the novel AB-type self-polycondensation route from the monomers, methyl 4-[4'-(omega-hydroxyalkoxy)biphenyl-4-yl]-4-oxobutyrate (HBOB-2,n). The mesophase characteristics of these polyesters was studied using DSC, polarized light optical microscopy and XRD techniques. The transition temperatures were found to decrease upon increasing the spacer length with an even polymer exhibiting higher transition temperature than the odd counterpart. The mesophase type also indicated an odd-even oscillation with the even members showing normal smectic phase and odd members exhibiting tilted smectic phase. The comparison of mesophasic characteristics of these polyesters with that of structurally similar AB-type polyesters indicated that the total number of atoms connecting the mesogen in a polymeric repeat unit governs the nature of the mesophase while the rigidity of the system dictates the magnitude of transition temperatures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AB approach; biphenyl mesogen; effect of connectivity; Liquid crystalline polyesters

Thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene and aliphatic dicarboxylic acid chlorides - Mulani, Khudbudin Baban; Momin, Mohasin Shamshuddin; Ganjave, Nitin V.; Chavan, Nayaku (Bulletin of Materials Science, 2015)
A series of thermotropic liquid crystalline polyesters derived from bis-(4-hydroxybenzoyloxy)-2-methyl-1,4-benzene(BHBOMB) and aliphatic dicarboxylic acid chlorides were investigated. All these polyesters were synthesized by interfacial polycondensation method and characterized by differential scanning calorimetry and wide-angle X-ray diffractometer. These polyesters consist of BHBOMB as a mesogenic diol and aliphatic diacid chlorides were used as flexible spacers. The length of oligomethylene units in polymer was varied from the trimethylene to the dodecamethylene groups. The transition temperatures and thermodynamic properties were studied for all these polymers. All these polyesters were soluble in chlorinated solvents such as chloroform, dichloromethane, dichloroethane, etc. More importantly, all these polyesters exhibited very large mesophase stability.
Keywords: dicarboxylic acid chloride; interfacial polycondensation; Liquid crystalline polyesters; rigid diol; thermotropic